SEBERAPA PENTINGNYA KEPUASAN DAN KUALITAS UNTUK MENCAPAI LOYALITAS DALAM BISNIS LAUNDRY? - Sulaiman, Haryaman Justisia; Afif, Muhammad Zhafir (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2025)
A positive development for a thriving market competition is the escalating level of competition in the laundry industry. Enhancements in the characteristics of service quality are crucial for providing novel client experiences and fostering loyalty. Hence, The aim of this study is to analyze the influence of service quality and customer satisfaction on customer loyalty in the laundry industry establishments located in the Bandung City region. The quantitative analysis method will be employed to collect data, which will be done by distributing questionnaires to active consumers of laundry businesses. The questionnaire encompasses factors such as service quality perception, satisfaction level, degree of loyalty, and customer demographic information. A significant positive influence of customer satisfaction and service quality on customer loyalty was revealed by the multiple linear regression analysis results. These findings provide significant insights for laundry firms aiming to enhance service quality and client satisfaction in order to boost customer loyalty. This contributes to the development of business actors and research- management.